Legal Uncertainty for Persons with Disabilities as Victims and Witnesses in Criminal Justice in Indonesia - Popy Rakhmawaty; Zudan Arief Fakrulloh (PT Publikasiku Academic Solution, 2024)
This study examines the legal uncertainty faced by persons with disabilities as witnesses and victims within Indonesia's criminal justice system. Although there are regulations that acknowledge the rights of persons with disabilities, their implementation often encounters various obstacles, ranging from inadequate accommodations to limited understanding among law enforcement officials. This legal uncertainty adversely impacts access to justice for persons with disabilities, who often feel marginalized within the legal process. Therefore, this research also discusses efforts to fulfill the rights of persons with disabilities as witnesses and victims, including the importance of training for law enforcement personnel, providing appropriate accommodations, and conducting comprehensive personal assessments to meet their specific needs. This study is expected to provide recommendations for policymakers to enhance legal protection and ensure accessibility for persons with disabilities within the criminal justice system.